Interpersonal, community, and societal dimensions of reproductive coercion: a sequential multimethod study of victim-survivors - Lévesque, Sylvie; Rousseau, Catherine; Boulebsol, Carole; Fernet, Mylène; Lapierre, Simon; Boulet, Ariane; Cousineau, Marie-Marthe; Legault, Jess (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Reproductive coercion (RC) is a gender-based form of violence intended to control or interfere with the reproductive autonomy of people with the capacity to become pregnant. It includes contraceptive sabotage, pregnancy pressure, and control of pregnancy outcomes. Although RC is examined mainly in intimate relationship contexts, it is not limited to them. We used an adapted critical ecological approach from a feminist perspective to explore how direct and indirect interactions between the interpersonal, community, and societal environments, all of which are shaped by cultural and social norms, can undermine contraceptive and reproductive autonomy. Methods We used a sequential multimethod research design that included a quantitative cross-sectional survey. In the first phase, a total of 427 individuals aged 29 years on average (M = 29.01; SD = 6.64) completed an online survey that contained quantitative measures of RC and intimate partner violence. Among the respondents, 33 provided answers to an open question to share RC experiences. In the second phase, a different convenience sample of 33 participants underwent individual qualitative interviews. We conducted a descriptive analysis of the quantitative data in SPSS 27 to determine the prevalence of each RC type. We independently coded the qualitative data from the open-ended question and individual interviews using NVivo 12. Results The findings improve the understanding of RC occurrence at different ecological levels as well as interactions between the levels. Interpersonal level. Many participants reported RC perpetuated by intimate partners or their entourage, mainly mothers-in-law and mothers. Entourage members use various strategies: psychological, spiritual, and emotional violence and control or financial extortion. In intimate relationships, the results show overlaps between intimate partner RC and violence: RC frequently occur in situations where their partner uses fear and/or control. Community level. The participants felt that healthcare workers (e.g., physicians, nurses) contributed to undermining their reproductive autonomy by withholding information about contraceptive methods, pressuring them to choose certain methods over others, or refusing to perform tubal ligations. Societal level. Reproductive autonomy is limited by the narrow choice of male contraceptive methods, overresponsibilisation of individuals who can become pregnant for the fertility control, lack of insurance coverage for certain contraceptive methods, and access barriers to reproductive services. Conclusion We need to better understand the contexts in which RC occurs to respond appropriately to this social and health issue. Changes are needed across levels to create environments that facilitate and promote reproductive health and autonomy.